Measuring quality of experiences towards Open and Distance Learning implementation among computer science students / Mohd Norafizal Abd Aziz, Haslinda Noradzan, Zazaleena Zakariah, Juhaida Ismail, Rozeleenda Abdul Rahman - Abd Aziz, Mohd Norafizal; Noradzan, Haslinda; Zakariah, Zazaleena; Ismail, Juhaida; Abdul Rahman, Rozeleenda (UiTM Press, 2021)
The emergence of COVID-19 pandemic has caused a huge impact to all sectors in the world since its first hit at the end of the year 2019. One of the sectors that has been experiencing major changes due to this pandemic is the education sector as face-to-face teaching and learning has switched to a fully online and distance approach to accommodate the continuity of previous practices in making the objectives achievable. The implementation of open and distance learning (ODL) during the first semester raised various perceptions from both students and lecturers as many factors needed to be considered to ensure the sessions meet the lesson objectives. Therefore, this study aims to investigate the quality of experiences towards ODL among computer science students by assessing three major factors; learning materials in ODL, platforms being used, and the delivery methods used during ODL. Using an empirical approach where responses from students were collected using a structured questionnaire, the analyzed data then contributed new discoveries to this study.